Modern theories of income distribution - Howard, Michael Charles (New York : St. Martin's Press, 1979)
This book seek to explain the prices which are paid to factors of production i.e. the various kinds of labour, natural resources and produced means of production.
Includes index.
Includes bibliographical references: p. [187]-193.
osa 14/11/17
Loans
Keywords: Distribution (Economic theory).; Income distribution; New York